DaPeCa‐3: promising results of sentinel node biopsy combined with 18F‐fluorodeoxyglucose positron emission tomography/computed tomography in clinically lymph node‐negative patients with penile cancer – a national study from Denmark. (22nd August 2015) - Jakobsen, Jakob K.; Alslev, Louise; Ipsen, Pia; Costa, Junia C.; Krarup, Kim P.; Sommer, Peter; Nerstrøm, Henrik; Toft, Birgitte G.; Høyer, Søren; Bouchelouche, Kirsten; Jensen, Jørgen B.
Abstract : Objectives: To estimate the diagnostic accuracy of sentinel node biopsy (SNB) combined with preoperative 18 F‐fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) for inguinal lymph node (LN) evaluation in patients with invasive penile squamous cell carcinoma (PSCC) with no clinical evidence of inguinal metastases (cN0) at two tertiary centres with complete clinical follow‐up. Patients and Methods: From April 2010 in Centre one and from January 2013 in Centre two, we prospectively enrolled patients diagnosed with invasive PSCC and scheduled for SNB at the only two university centres treating penile cancer in Denmark. All patients had FDG PET/CT before SNB. The sentinel LNs were preoperatively located by planar lymphoscintigraphy in 134 groins (68 patients) and by single‐photon emission CT/CT in 120 groins (61 patients). The primary endpoints were the sensitivity, specificity, and false‐negative rate of SNB combined with FDG PET/CT. The secondary endpoint was SNB‐related morbidity. Results: We examined 254 groins in 129 patients by SNB combined with FDG PET/CT. The median (interquartile range, IQR) follow‐up of survivors was 23 (14–35) months. Of 201 LN‐negative groins, two were false negatives, and despite radio‐chemotherapy treatment, both patients died from penile cancer. Four of 23 radiotracer‐silent groins, had a FDG PET/CT‐positive LNs and were surgically explored. In one of four of the explored groins, a positive LN was found. Combined FDG PET/CT‐SNB sensitivity was 94.4% (95% confidence interval [CI] 81–99%) per groin. The false‐negative rate was 5.6% (95% CI 1–19%) per groin. In 15 patients (11.6%) there were 25 SNB‐related complications of Clavien–Dindo grades I–IIIa. The only Clavien–Dindo IIIa complication was an inguinal lymphocele treated by aspiration. Conclusion: In this study, we present a favourable SNB false‐negative rate of 5.6% in a national cohort of clinically LN‐negative patients with invasive PSCC with a pre‐SNB FDG PET/CT scan. The combination of FDG PET/CT and SNB seems to be a promising diagnostic approach. Even so, a false‐negative SNB was fatal in two of two cases and we are determined to continue the development of our SNB technique. The SNB‐related morbidity was limited.